Prediction of pre-hospital blood transfusion in trauma patients based on scoring systems - Plodr, Michal; Berková, Jana; Hyšpler, Radomír; Truhlář, Anatolij; Páral, Jiří; Kočí, Jaromír (BMC emergency medicine, 2023)
BACKGROUND: Pre-hospital blood transfusion (PHBT) is a safe and gradually expanding procedure applied to trauma patients. A proper decision to activate PHBT with the presently limited diagnostic options at the site of an incident poses a challenge for pre-hospital crews. The purpose of this study was to compare the selected scoring systems and to determine whether they can be used as valid tools in identifying patients with PHBT requirements. METHODS: A retrospective single-center study was conducted between June 2018 and December 2020. Overall, 385 patients (aged [median; IQR]: 44; 24-60; 73% males) were included in this study. The values of five selected scoring systems were calculated in all patients. To determine the accuracy of each score for the prediction of PHBT, the Receiver Operating Characteristic (ROC) analysis was used and to measure the association, the odds ratio with 95% confidence intervals was counted (Fig. 1). RESULTS: Regarding the proper indication of PHBT, shock index (SI) and pulse pressure (PP) revealed the highest value of AUC and sensitivity/specificity ratio (SI: AUC 0.88; 95% CI 0.82-0.93; PP: AUC 0.85 with 95% CI 0.79-0.91). CONCLUSION: Shock index and pulse pressure are suitable tools for predicting PHBT in trauma patients.
Keywords: senioři; Male; Female; krevní transfuze; rány a poranění; Aged; Blood Transfusion; mužské pohlaví; ženské pohlaví; Blood Pressure; Hospitals; nemocnice; Retrospective Studies; krevní tlak; retrospektivní studie; Sensitivity and Specificity; Wounds and Injuries; lidé; Humans; senzitivita a specificita